(untitled) (Bulletin of criminological association of Ukraine, 2024)
In this article, it has been emphasized that the mechanism of committing bank card fraud is characterized by the presence of direct dependencies between the methods of committing them and the time, place and circumstances, which, in turn, determine the typical traces of the specified criminal offenses. It has been emphasized that the mandatory and informative elements of the forensic characterization are the time, place and circumstances of committing bank card fraud. An analysis of scientific approaches to interpreting the essence and content of the time, place and circumstances of committing a criminal offense as an element of forensic characterization has been carried out. The typical time, place and circumstances of committing bank card fraud have been determined. It has been established that bank card fraud is characterized by a wide geography and covers all regions of Ukraine. It has been noted that criminals can actually be located outside of Ukraine. It has been proven that the time of committing bank card fraud depends on the specific fraudulent scheme and may coincide with: working hours of banking institutions, time of withdrawing funds from ATMs, time of making online purchases, time of processing “assistance (social payment)”, etc. It has been established that the situation of committing bank card fraud is a system of circumstances that determine the scope of their commission. The nature of social relations that the criminal offenses under investigation encroach on, the level of their regulation directly determine the conditions for committing an offense in this area. The situation of bank card fraud has been determined simultaneously by the scope of banking relations and information technologies. It has been found that a considerable number of the offenses under investigation are committed in cyberspace, using cyber tools. It has been emphasized that an equally important role in the mechanism of committing fraud with bank cards is played by the state of war in Ukraine, which led to the internal displacement of a large number of citizens, a decrease in the socio-economic standard of living of citizens, an increase in the types of social payments and humanitarian assistance to certain categories of persons, etc. It has been noted that criminals actively use these conditions when searching for potential victims, choosing fraudulent schemes and methods of their implementation.